How does globalisation affect regional inequality within a developing country? evidence from China - Zhang, Xiaobo; Zhang, Kevin H. (Informa UK Limited, 2003)
Developing countries are increasingly concerned about the effects of globalisation on regional inequality. This article develops an empirical method for decomposing the contributions of two major driving forces of globalisation, foreign trade and foreign direct investment (FDI), on regional inequality and applies it to China. Even after controlling for many other factors, globalisation is still found to be an important factor contributing to the widening regional inequality. The article ends by investigating the role of factor market segmentations in aggravating the distributional effect of changing regional comparative advantages in the process of globalisation. -- Authors' Abstract